Coating layer-containing microcrystalline glass with coloring additive, and preparation method therefor

JP2024096170A5Pending Publication Date: 2025-02-04CHONGQING AUREAVIA HI TECH GLASS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024067815
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-01-29
Filing Date
2024-04-18
Publication Date
2025-02-04

AI Technical Summary

Technical Problem

Existing methods for creating water- and oil-repellent coatings on microcrystalline glass with high crystallinity fail to maintain effective adhesion and durability, as the Si-O structure in the glass interface limits the bonding capacity of hydrophobic and oleophobic coatings, leading to reduced performance over time.

Method used

A composite coating layer is applied to microcrystalline glass, comprising a water- and oil-repellent layer, an intermediate layer with specific ionic crystal lattice energy, and an undercoat layer containing Si-O bonds or mixed silicon oxide, enhancing bonding and durability.

Benefits of technology

The composite coating layer achieves excellent water and oil repellency and abrasion resistance, even on high-crystallinity microcrystalline glass, maintaining performance beyond conventional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide a glass with a water-repellent and oil-repellent coating applied to a microcrystalline glass, a preparation method and an application therefor.SOLUTION: A microcrystalline glass or a glass ceramic contains a water-repellent and oil-repellent composite coating layer on the surface. From the outmost surface of the glass, it sequentially includes a water-repellent and oil-repellent layer, an intermediate layer, and a primer layer. Here, the intermediate layer is the intermediate layer containing ionic crystals with a lattice energy of 700-3000 kJ / mol, and the primer layer includes compounds containing Si-O bonds or a mixed silicon oxide layer. The present invention can form a firm, durable and excellent water-repellent and oil-repellent coating film even if the coating interface of microcrystalline glass has few Si-O structures, and can achieve excellent water-repellent and oil-repellent properties regardless of whether the high-crystallinity glass has undergone ion exchange or not.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a coating glass having water- and oil-repellent properties and a manufacturing method and application thereof, and in particular to a microcrystalline glass having a highly crystallized microcrystalline glass surface with a water- and oil-repellent composite coating layer. [Background technology]

[0002] Glass generally has high surface activity, which means that it is easy to get dirty and difficult to clean after the surface gets dirty. For example, in many application scenarios such as cooking utensils, glass products in range hoods, mobile phones, tablets, and touch screen man-machine interaction windows, coating the glass surface with a layer of "water-repellent" film reduces the activity of the glass surface and improves its "water-repellent and oil-repellent" ability and its hydrophobicity. After the hydrophobicity is improved, when you touch the glass surface with your finger, you can clearly feel the improvement in "slipperiness", because the hydrophobicity is improved and the sliding friction coefficient is reduced, which is a function that improves the user experience for touch interfaces.

[0003] In the prior art, in order to improve the water and oil repellency of the glass surface, a method of directly coating the glass surface is usually adopted. The common coating film material is PFPE (perfluoropolyether, a type of fluorine-containing polyether silicon oxide), and the structure of the fluorine-containing polyether silicon oxide (e.g., alkoxysilicide) is as follows: [ka] Here, R can be carbon, hydrogen or silicon, and Y can be an ether bond, a sulfur-containing hydrocarbon group, a sulfur-containing alkoxy, a nitrogen-containing hydrocarbon group, a nitrogen-containing alkoxy, an epoxyalkyl group, an acyloxy hydrocarbon group, a hydrocarbon group, a thio group, or the like.

[0004] The bonding process between PFPE and glass is a chemical reaction process, which involves hydrolysis of PFPE (PFPE-Si-OR+HO->PFPE-Si-OH+ROH), followed by a dehydration condensation reaction (PFPE-Si-OH+HO-Si→HO+PFPE-Si-O-Si-, as shown in Figure 1), and finally, the Si-O structures on the interface between the PFPE film and glass form valence bonds, rather than a physical phenomenon that relies on intermolecular van der Waals forces as in most vacuum coatings.

[0005] In the prior art, the coating methods are generally as follows: Because there are a large amount of Si-O structures in glass, PFPE has the conditions to directly react with glass to form a film, but the SiO2 mass ratio in glass generally does not exceed 70% at most, and in order to improve the coating effect and durability, the following two coating methods are generally adopted:

[0006] a) Dry method: Also known as the vacuum coating method, a layer of SiO2 is coated on the surface of the current glass in a vacuum to increase the Si-O ratio, and then a layer of PFPE is coated in a vacuum environment.

[0007] b) Wet method: also known as spray coating method, this method uses plasma to bombard the glass surface in the atmosphere, cleans the glass surface, and roughens the glass surface, increasing the surface area of ​​the glass at a microscopic level and indirectly increasing the Si-O ratio, and then sprays a layer of PFPE solution.

[0008] Existing Patent Document 1 discloses the structure of an anti-soiling coating layer on the surface of transparent microcrystalline glass, and is characterized in that a colorless and transparent anti-soiling layer (11) having a thickness of 4 to 30 nm is attached to the outer surface layer of the microcrystalline glass body (1), and the anti-soiling layer (11) is a fluorosilicone hydrolyzed compound. The patent also describes the microcrystalline glass device, which is characterized in that a silicon dioxide layer having a thickness of 3 to 20 nm is present below the anti-soiling layer (11).

[0009] However, the characteristic of the microcrystalline glass that is mainly protected by this patent is that "the mass ratio of the crystal phase and the glass phase of the microcrystalline glass body is 0.25-1.2", which is a microcrystalline glass with a medium and low level of crystallinity, the glass phase of the microcrystalline glass body uniformly surrounds the outer periphery of the crystal phase, the glass phase contains alkali metal ions such as sodium, lithium, and potassium, the mass of the alkali metal oxide of the glass phase divided by (the mass of alumina plus the mass of silica) is 6%-30%, the crystallinity of the microcrystalline glass is 20-54.54%, and the glass phase in the microcrystalline glass still has a sufficient amount of Si-O structure, which can support the formation of better valence bonds between PFPE and the microcrystalline glass. However, this invention does not mention any related issues regarding the microcrystalline glass with a high degree of crystallinity.

[0010] The existing Patent Document 2 discloses the following solution to the problem of poor bonding strength and durability of the hydrophobic / oleophobic coating layer or anti-fingerprint coating layer on the glass surface due to prestressing by ion exchange: "Currently, it has been found that chemical prestressing significantly reduces the durability of the hydrophobic / oleophobic coating layer or anti-fingerprint coating layer. This shows shorter durability in corresponding tests and neutral salt spray tests, for example, which are specifically described in Patent Documents 3 and 4." Based on this object, the present invention not only solves the shortcomings of the prior art, but also provides a glass substrate having a chemically prestressed hydrophobic / oleophobic coating layer with sufficient long-term durability. Furthermore, a method for manufacturing a coated and chemically prestressed glass substrate should be provided. The above object is achieved in the following surprising manner. That is, the glass substrate is chemically prestressed by passing through all layers of glass by the method of ion exchange, and then the functional coating layer on the glass substrate is activated before the hydrophobic / oleophobic coating layer that functions as the anti-fingerprint coating layer is coated. That is, first, a "functional coating layer" is made on glass that has not been ion-exchanged, then "ion exchange" is performed, followed by "activation of the functional coating layer" and then "coating of the hydrophobic / oleophobic coating layer". Here, the patent mentioned that it has been found that the functional layer, particularly the top functional layer, preferably contains one or more Si compounds, particularly preferably contains one or more silicon oxide compounds, and that it is particularly advantageous that the Si compounds may be selected from, for example, silicon oxides. Preferably, silicon oxides SiOx (x is 2 or less), SiOC, SiON, SiOCN and Si3N4, and hydrogen that can be bonded to SiOx (x is 2 or less), SiOC, SiON and SiOCN in any amount. In a preferred embodiment, the functional layer, particularly the top functional layer, is a silicon mixed oxide layer. Thus, the patent disclosed that the "functional coating layer" is mainly composed of inorganic components containing a Si-O structure. The patent also stated that "chemical prestressing usually weakens the long-term stability of the hydrophobic / oleophobic coating layer. This defect has been eliminated by the present invention.According to the present invention, the surface of at least one functional layer is activated after chemical prestressing, so that the interaction between the surface of the functional layer and the hydrophobic / oleophobic coating layer to be applied occurs. The patent believes that the accumulation of potassium ions on the surface of the top functional layer reduces the number of available bonding sites, such as Si-OH in the Si-containing functional layer, which prevents the covalent bonding of the hydrophobic / oleophobic coating layer, resulting in poor adhesion and low long-term stability of the hydrophobic / oleophobic coating layer. In addition, the surface of the top functional layer is usually burdened with contamination by organic or inorganic contaminants, which prevents the desired interaction. Therefore, the patent adjusts the order of ion exchange and uses surface activation to activate Si-O to enhance the bonding ability of the hydrophobic / oleophobic coating layer, that is, the patent is completely committed to the technical optimization of glass rich in Si-O structure and functional undercoat layer rich in Si-O structure. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] China Utility Model No. 208747932 [Patent Document 2] China Patent Application Publication No. 106715352 [Patent Document 3] International Publication No. 2012 / 163946 [Patent Document 4] International Publication No. 2012 / 163947 Summary of the Invention [Problem to be solved by the invention]

[0012] The glass coating principles in the prior art of the present invention are all based on water- and oil-repellent coatings based on inorganic glass. Generally speaking, the water- and oil-repellent effect can be such that the initial water drop angle test is more than 110°, and can reach about 115°, and even after 5000 times of friction, the water drop angle can still reach more than 100°. However, even for microcrystalline glass with a high crystallinity of more than 60%, when the principles and methods of the prior art are followed (using surface activation to activate Si-O to enhance the binding ability of the hydrophobic and oil-repellent coating layer), the effect is very poor, and the initial water drop angle can generally only reach about 100°, and after 2500 times of friction, the water drop angle is only about 60°. Although microcrystalline glass is a type of glass and the Si-O content in its components is not less than that of general inorganic glass, the reason for such a large difference can be understood as being that the conventional methods all provide water- and oil-repellent coating layer solutions created for interfaces rich in Si-O structures, and these solutions cannot function effectively in situations of high crystallinity or where the interface lacks a glass phase or Si-O structures.

[0013] In order to solve the above-mentioned conventional technical problems, the present invention provides the following technical solutions. [Means for solving the problem]

[0014] A microcrystalline glass containing a water- and oil-repellent composite coating layer on its surface, the microcrystalline glass comprising, in order from the outermost surface, a water- and oil-repellent layer, an intermediate layer, and an undercoat layer, the intermediate layer being an ion crystal intermediate layer containing a crystal lattice energy of 700 to 3000 kJ / mol, and the undercoat layer containing a compound containing Si-O bonds or a mixed silicon oxide layer.

[0015] Preferably, for any of the above microcrystalline glasses, the degree of crystallinity may be greater than 60%, or greater than 70%, or greater than 80%.

[0016] Preferably, for any of the above microcrystalline glasses, the intermediate layer is an intermediate layer formed from an original coating film material of ionic crystals having a crystal lattice energy of 725 to 3000 kJ / mol, more preferably 770 to 3000 kJ / mol; Alternatively, it is a fluoride intermediate layer formed using a compound having a crystal lattice energy of 9400 to 11400 KJ / mol, preferably a silicofluoride, as the original coating film material.

[0017] Preferably, for any of the above-mentioned microcrystalline glasses, the intermediate layer contains an alkali metal fluoride or an alkaline earth metal fluoride compound, or is an intermediate layer formed using ion crystals selected from alkali metal silicofluorides and alkaline earth metal silicofluorides as the original coating film material.

[0018] Preferably, for any of the above microcrystalline glasses, said intermediate layer is an ion-crystalline intermediate layer having a crystal lattice energy less than 1050 KJ / mol, preferably less than 940 kJ / mol.

[0019] Preferably, for any of the above-mentioned microcrystalline glasses, the intermediate layer is a crystal formed using at least one of LiF, NaF and / or KF ionic crystals as the original coating film material, or an intermediate layer formed using at least one of MgF2, CaF2, SrF2 or BaF2 as the original coating film material, or a fluoride intermediate layer formed using at least one of Li2SiF6, Na2SiF6, K2SiF6, Rb2SiF6, Cs2SiF6, BeSiF6, MgSiF6, CaSiF6, SrSiF6 or BaSiF6 as the original coating film material, with an intermediate layer formed using NaF or KF ionic crystals as the original coating film material being preferred.

[0020] Preferably, for any of the above microcrystalline glasses, the intermediate layer is a polar or non-polar compound, preferably a polar compound.

[0021] Preferably, for any of the above microcrystalline glasses, the thickness of the intermediate layer is 1 to 5 nm, and more preferably 1 to 2 nm.

[0022] Preferably, for any of the above microcrystalline glasses, the thickness of the undercoat layer is 3 to 15 nm, preferably 5 to 10 nm, and more preferably 5 to 8 nm.

[0023] Preferably, in any of the above microcrystalline glasses, the water- and oil-repellent layer has a thickness of 10 nm or more, preferably 15 nm or more, and may be 10 nm to 25 nm.

[0024] Preferably, in any of the above microcrystalline glasses, when the undercoat layer is a multi-layered layer, the compound or mixed silicon oxide layer containing Si-O bonds is the outermost undercoat layer, and the mixed silicon oxide is silicon oxide SiO x (x is 2 or less) and at least one oxide of an element other than silicon and / or magnesium fluoride; The other element is preferably an element selected from the group consisting of aluminum, tin, magnesium, phosphorus, cerium, zirconium, titanium, cesium, barium, strontium, niobium, zinc, and boron, and the mixed silicon oxide is preferably a silicon oxide SiO x and an oxide of aluminum are more preferred.

[0025] Preferably, for any of the above microcrystalline glasses, the compound containing the Si-O bond is SiOx (x is 2 or less), or any one of the substances selected from the group consisting of SiOC, SiON, SiOCN, and / or Si3N4, or a hydrogen bond bonded to any one of the substances selected from the group consisting of SiOx (x is 2 or less), SiOC, SiON, and / or SiOCN in any ratio.

[0026] Preferably, in any of the above microcrystalline glasses, the water- and oil-repellent layer is a fluorine-based polymer layer, preferably a fluorine-containing polyether silicon oxide layer having a molecular weight of 2000 or more, and the coating layer has a thickness of 10 nm or more.

[0027] Preferably, in any one of the above microcrystalline glasses, the composition of the microcrystalline glass is composed of the following oxides in mol % ratio: 40 to 75%, preferably 45 to 72% SiO2; 2 to 20%, preferably 4 to 15% Al2O3; 0 to 20%, preferably 0.4 to 1.6%, of B2O3; 0 to 10%, preferably 0.8 to 1.5%, of P2O5; 0-15%, preferably 0.9-4% ZrO2+TiO2; 0 to 5%, preferably 0.1 to 2% MgO; 0 to 4%, preferably 0.9 to 3.0% ZnO; 0 to 5%, preferably 0.01 to 1%, of rare earth oxides; 0-5.5% Na2O, 0-4% K2O, 2 to 34%, preferably 10 to 34%, LiO; It contains 4 to 40%, preferably 15 to 40%, of Na2O+K2O+Li2O.

[0028] Preferably, in any of the above microcrystalline glasses, the rare earth oxides are one or more selected from CeO2, Y2O3, La2O3, Ta2O3, Tm2O5, and Nd2O5.

[0029] Preferably, for any of the above microcrystalline glasses, the microcrystalline glass may further contain a coloring additive, and the coloring additive is preferably one or more selected from Nd2O3, Fe2O3, CoO, NiO, V2O5, MnO2, TiO2, CuO and Cr2O3.

[0030] Preferably, for any of the above microcrystalline glasses, the molar content of the color additive relative to the total components of the glass does not exceed 5%, and in terms of the molar content relative to the total components of the glass, the color additive preferably contains 0.5 mol% or more of CoO and / or Cr2O3, and more preferably contains 1 mol% or more of one or more selected from Fe2O3, NiO, or MnO2.

[0031] Preferably, for any of the above microcrystalline glasses, the microcrystalline glass contains a fining agent, and the fining agent is As2O3, Sb2O3, SnO2, chloride, fluoride, SO3 - Containing compounds and NO3 - It is preferable that the compound is one or more selected from the group consisting of SnO2, SO3 - Containing compounds, chlorides, and NO3 - It is preferable that the content of the clarifier is one or more selected from the above-mentioned compounds, and the content of the clarifier is preferably 0 to 2 mol %.

[0032] Preferably, for any of the above microcrystalline glasses, the main crystal phase of the microcrystalline glass is one or more selected from β-quartz solid solution, β-spodumene solid solution, β-eucryptite, spinel, rutile, mullite, olivine, enstatite, cordierite, petalite, lithium silicate, lithium disilicate, quartz, zirconia, and magnetite, and the average crystal grain size is preferably less than 100 nm, more preferably 50 nm or less, and particularly preferably 30 nm or less.

[0033] Preferably, for any of the above microcrystalline glasses, said microcrystalline glasses are ion-exchanged or non-ion-exchanged glasses.

[0034] More preferably, in any of the above microcrystalline glasses, the microcrystalline glass is a glass ceramic having a crystallinity of less than 60%.

[0035] The present invention further provides a method for producing any one of the above microcrystalline glass, which comprises the steps of: Step 1) of coating the microcrystalline glass with a Si-O containing oxide or mixed silicon oxide layer to form a primer layer on the surface of the microcrystalline glass; Step 2) of coating an intermediate layer on the surface of the undercoat layer obtained in step 1); and step 3) coating a water- and oil-repellent layer on the surface of the intermediate layer obtained in step 2).

[0036] Preferably, in the above manufacturing method, the coating is performed by vacuum deposition.

[0037] Preferably, in any of the above manufacturing methods, the microcrystalline glass is ion-exchanged microcrystalline glass.

[0038] Preferably, in any one of the above-mentioned manufacturing methods, the microcrystalline glass is coated with the undercoat layer, the intermediate layer, and the water- and oil-repellent layer, Step (I) of melting each glass raw material at a high temperature of 1600±50°C and then annealing it at 400-650°C to obtain a homogenized raw glass plate; (II) obtaining a shaped raw glass plate from the raw glass plate by an overflow downdraw method, a float method or a rolling method; The raw glass plate is microcrystallized by two heat treatments to obtain a microcrystalline glass preform, which is then either ion-exchanged or not ion-exchanged and used as is as a raw material for microcrystalline glass to coat the required undercoat layer, intermediate layer and water- and oil-repellent layer on the surface in that order, and is fired by a method including the step (III) in which the first heat treatment temperature is 500 to 1000°C and the second heat treatment temperature is 550 to 1100°C.

[0039] Preferably, any of the above microcrystalline glasses or any of the above microcrystalline glasses obtained by the manufacturing methods are used in the displays of mobile phones, tablet computers, notebook computers, portable game consoles, portable digital devices, in-vehicle displays, windshields, or camera displays.

[0040] The present invention can form a strong, durable, and excellent water- and oil-repellent coating film even when there are very few Si-O structures at the coating interface of a microcrystalline glass or glass ceramic, and can achieve excellent water- and oil-repellency regardless of whether the highly crystallized glass has been ion-exchanged. [Brief description of the drawings]

[0041] [Figure 1] FIG. 1 is a diagram of the reaction process by which PFPE hydrolysis products attach to glass. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0042] The composition of microcrystalline glass seems to be very similar to that of general inorganic glass, and generally all of them have SiO2<70wt%, and it seems that it can produce a very good water-repellent and oil-repellent film according to the conventional coating method, but since microcrystalline glass has a large amount of crystals inside, usually, in the process of forming microcrystalline glass, SiO2 enters into the crystal and changes the structure, so that Si-O cannot be properly liberated and bonded with the water-repellent and oil-repellent layer, and the ratio of these fine crystals is usually 20-100%, that is, when the crystal ratio is high, the main reason for the deterioration of the quality of the water-repellent and oil-repellent coating layer is that the glass phase of microcrystalline glass is reduced and the Si-O at the interface is greatly reduced. The present invention provides a solution to this "rootless" problem.

[0043] Specifically, the present invention provides the following technical solutions:

[0044] This is a composite coating design of a water- and oil-repellent film on the surface of a highly crystallized microcrystalline glass or glass ceramic, in which a water- and oil-repellent layer, an intermediate layer, and an undercoat layer are formed on the glass in this order from the outermost surface, that is, the undercoat layer is on the inside of the microcrystalline glass or glass ceramic, and the water- and oil-repellent layer is on the outermost surface.

[0045] That is, the method of the present invention realizes the formation of a water- and oil-repellent film even when the crystallinity of the microcrystalline glass or glass ceramic is as high as 60% or more, and the crystallinity of the microcrystalline glass or glass ceramic may be 60% or more, 70% or more, or particularly 80% or more. Of course, since the present invention solves the water- and oil-repellent problem of microcrystalline glass or glass ceramic having a high crystallinity of 60% or more, which makes it difficult to form a water- and oil-repellent film, it is natural that the method of the present invention can also form a composite coating layer with an excellent water- and oil-repellent film on microcrystalline glass or glass ceramic having a crystallinity of 60% or less.

[0046] Here, the intermediate layer is preferably an ionic crystal having a crystal lattice energy of 700 to 3000 kJ / mol (the compositional components of the ionic crystal layer as the intermediate layer are preferably limited to alkali metal fluorides and alkaline earth metal fluorides depending on the magnitude of the crystal lattice energy), and is preferably 725 kJ / mol or more, and more preferably 770 kJ / mol or more (excluding radioactive substances).

[0047] Crystal lattice energies of some common ionic crystals / (kJ mol -1 ) are as shown in Table A below.

[0048] [Table 1A]

[0049] Here, the crystal lattice energy of the ionic crystal is preferably less than 1050 kJ / mol (basically, it is preferable to limit the ionic crystal layer to three types of alkali metal fluorides, LiF / NaF / KF), and more preferably less than 940 kJ / mol (basically, it is preferable to limit the ionic crystal layer to two types, NaF / KF); For the intermediate layer, alkali metal silicofluorides and alkaline earth metal silicofluorides such as Li2SiF6, Na2SiF6, and K2SiF6 may be used.

[0050] Preferably, the intermediate layer is a polar and non-polar compound (preferably alkali metal fluorides - non-polar and alkaline earth metal fluorides - polar), More preferably, the compound is a non-polar compound (preferably an alkali metal fluoride - reduced to non-polar), Here, the thickness of the intermediate layer is preferably 1 to 5 nm, and more preferably 1 to 2 nm. Here, preferably, the undercoat layer contains a Si compound or is made of a Si compound, and the Si compound is preferably selected from the following: -SiOx (x is 2 or less), in the case of a multilayer, at least the outermost or top layer comprises or consists of silicon oxide; -SiOC, SiON, SiOCN and Si3N4, and SiOx (x is 2 or less), hydrogen bonds formed with SiOC, SiON and SiOCN in any ratio ("hydrogen bonds" here refers to hydrogen bonds formed between any component in the air, such as moisture, and the silicon oxide of glass), or mixed silicon oxides, consisting of a silicon oxide SiOx (x is 2 or less) and at least one oxide of an element other than silicon and / or magnesium fluoride, whereby the other element is preferably at least one selected from aluminum, tin, magnesium, phosphorus, cerium, zirconium, titanium, cesium, barium, strontium, niobium, zinc and boron, and particularly preferably a mixture of a silicon oxide SiOx (x is 2 or less) and at least one oxide of the element aluminum, Here, the total thickness of the undercoat layer is preferably 3 to 15 nm, more preferably 5 to 10 nm, and even more preferably 5 to 8 nm.

[0051] Here, the water- and oil-repellent layer is also called an AF layer (anti-fingerprint layer), and the AF layer is a layer formed of a fluorine-based polymer, and the fluorine-based polymer may be selected from perfluoropolyether, vinylidene fluoride polymer, tetrafluoroethylene polymer, hexafluoropropylene polymer, chlorotrifluoroethylene polymer, and combinations thereof, and is preferably perfluoropolyether (abbreviated as PFPE). More preferably, the water- and oil-repellent layer is PFPE with a molecular weight of 2000 or more, and the thickness of the coating layer is 10 nm or more, preferably 15 nm or more, and may be 10 nm to 25 nm.

[0052] Preferably, the microcrystalline glass is transparent or opaque, is ion-exchanged or unexchanged, and is prestressed or non-prestressed.

[0053] Also, preferably, according to the method according to at least one of the above technical solutions, the microcrystalline glass is characterized in that it is a glass having or consisting of the following glass composition (in mol%): 40 to 75%, preferably 45 to 72% SiO2; 2 to 20%, preferably 4 to 15% Al2O3; 0 to 20%, preferably 0.4 to 1.6%, of B2O3; 0 to 10%, preferably 0.8 to 1.5%, of P2O5; 0-15%, preferably 0.9-4% ZrO2+TiO2; 0 to 5%, preferably 0.1 to 2% MgO; 0 to 4%, preferably 0.9 to 3.0% ZnO; 0 to 5%, preferably 0.01 to 1%, of rare earth oxides; 0-5.5% Na2O, 0-4% K2O, 2 to 34%, preferably 10 to 34%, LiO; 4 to 40%, preferably 15 to 40% Na2O+K2O+Li2O.

[0054] Here, the rare earth oxide is one or more selected from CeO2, Y2O3, La2O3, Ta2O3, Tm2O5, and Nb2O5.

[0055] In some preferred embodiments, the composition of the glass includes additives of coloring oxides, such as Nd2O3, Fe2O3, CoO, NiO, V2O5, MnO2, TiO2, CuO, and Cr2O3, and rare earth oxides, the content of which is 0-5 mol % or, in the case of "black glass", the content of which is 0-5 mol %, such as As2O3, Sb2O3, SnO2, Cl, etc. - Containing compounds, F - Containing compounds, SO3 - Compounds contained, NO3 - and a clarifier, the content of which is 0 to 2 mol %, which is one or more of the contained compounds.

[0056] In addition, in some preferred embodiments, according to the method according to any one of the above technical solutions, the main crystalline phase of the microcrystalline glass is preferably one or more selected from β-quartz solid solution, β-spodumene solid solution, β-eucryptite, spinel, rutile, mullite, olivine, enstatite, cordierite, petalite, lithium silicate, lithium disilicate, quartz, zirconia, and magnetite, and the average crystal grain size is preferably less than 100 nm, particularly preferably 50 nm or less, and very particularly preferably 30 nm or less.

[0057] The present invention uses a combination of a water-repellent and oil-repellent layer, such as a SiO2 layer or a SiOx layer or a silicon oxide-containing mixture layer (collectively referred to as a "silicon oxide layer", SiO2 is used as an example here, but is not limited to SiO2 in practice) undercoat layer + intermediate layer (abbreviated as "RF layer", NaF is used as an example) + PFPE, where the SiO2 layer should not be too thick, generally 5 nm, not exceeding 15 nm, SiO2 exhibits a net-like or chain-like structure at the microscopic level, the 5 nm SiO2 coating layer is very thin, and the SiO2 coating layer can retain its mesh structure (if the coating is too thick, the SiO2 coating layers will overlap each other and the mesh will disappear), and then coat a thinner intermediate layer RF, where RF is a compound with not too high crystal lattice energy, especially a non-polar compound, and RF is selected as a compound with not too high crystal lattice energy, and RF reacts with water in the atmosphere to form R + , F - , H + , O.H. - It is easy to become. RF+H2O⇔R + +OH - +H + +F -

[0058] Because there are cavities in the undercoat layer, R + , F - , H + , O.H. -can penetrate very easily to the interface of microcrystalline glass and react with the Si-O-Si structure of the crystals. By opening the Si-O of the crystal structure, it can react better with the water- and oil-repellent layer, forming the basis for film formation. ≡Si-O-Si≡+R + +OH - →≡Si-OH+RO-Si≡, ≡Si-O-Si≡+H + +F - →SiF4+H2O→H2SiO3+H2SiF6, When sufficient Si-O is generated at the microcrystalline glass interface and undercoat layer to adhere to the microcrystalline glass base, sufficient valence bonds are generated when reacting with the topmost water- and oil-repellent layer PFPE, thereby significantly improving the performance and abrasion resistance of the water- and oil-repellent layer.

[0059] The intermediate layer with appropriate crystal lattice energy is the key to the operating principle of the present invention. If the crystal lattice energy is somewhat low, the intermediate layer is active and prone to reaction. Only when the crystal lattice energy is moderate can the stability of the material be maintained. Therefore, the intermediate layer of the present invention requires that the crystal lattice energy is within a certain range. Intermediate layer materials within this crystal lattice energy range still have high hydrolysis resistance and activity, and have a certain corrosiveness after hydrolysis, so they should not be coated too thickly, otherwise the effect will be poor. Generally speaking, it should not exceed 5 nm. If it is too thick, the reaction products cannot be completely consumed during the entire reaction process, which will erode the glass and become serious corrosion points on the glass surface, and also lead to a decrease in the weather resistance of the coating layer.

[0060] About the term "microcrystalline glass or glass ceramics" In the present invention, the terms "microcrystalline glass" and "glass ceramics" have the same meaning, and refer to glasses having a crystalline phase, unlike glasses without a crystalline phase or amorphous glasses. Therefore, the terms "microcrystalline glass or glass ceramics", "microcrystalline glass" or "glass ceramics" used in the present specification have the same meaning.

[0061] On crystal lattice energy Crystal lattice energy refers to the energy absorbed when an ion crystal becomes a positive ion gas and a negative ion gas under standard conditions, and is a parameter for measuring the stability of a crystal lattice. Factors that affect the magnitude of the crystal lattice energy include ion radius, ion charge, and the electronic layer structure of the ion. The formula obtained by fitting the method for calculating crystal lattice energy in the book "Topological Study on the Crystal Lattice Energy and Magnetic Susceptibility of Alkaline Earth Metal Halides" written by Qin Zhenglong and Liu Changjun is as follows: U=1129.1-441.8 0 F+3600.5 1 F, n F = Σ(E i ×E j ×E k ×…) -0.5 , n F is the topological exponent coefficient and E is the valence energy level value.

[0062] The fluoride crystal lattice energies (KJ / mol) calculated using this method are shown in Table B.

[0063] [Table 1B]

[0064] The regression equation obtained by fitting the method has good correlation, and can also be applied to calculate the crystal lattice energy of silicofluoride. The results are shown in Table C.

[0065] [Table 1C]

[0066] It should be noted that the original material of the coating film and the material finally formed in the undercoat layer of the glass interface are not necessarily the same concept. Take the alkali metal silicofluoride R2SiF6 calculated above as an example. Normally, R2SiF6 is a relatively stable solid at room temperature, and when heated to about 300°C during coating, it decomposes, and becomes R2SiF6->2RF+SiF4 (gas), that is, it seems to be a material with high crystal lattice energy, but in fact, when it is formed into a film, the material that plays an important role has already undergone a qualitative change, and its crystal lattice energy is within the optimal operating range claimed by the present invention. For example, sodium silicofluoride Na2SiF6 is an odorless and tasteless white particle or crystalline powder, and after burning (above 300°C), it decomposes into sodium fluoride NaF and silicon tetrafluoride SiF4.

[0067] Based on the above explanation of the principle of the present invention, whether the interface of the coated microcrystalline glass is ion-exchanged or not does not affect the implementation and effect of the present invention. Small ions in the glass can only be exchanged with large ions in the external salt bath when they are in a state where ion migration is possible. Temperature is the key factor for realizing ion migration, and generally speaking, it is relatively easy to realize ion migration in the glass phase at a relatively low temperature (for example, below the temperature of the strain point, i.e., starting from about 200 degrees Celsius, for example, 360°C), and the alkali metal elements in the microcrystalline phase are part of the crystal structure before becoming mobile ions, and can only move and become freely exchangeable ions after removing the restrictions due to the crystal structure with higher energy, which temperature is usually closer to the softening point of the glass (for example, above 600 degrees Celsius). Therefore, most of the ion exchange usually occurs in the glass phase, and even when the temperature of the salt bath is very high, it occurs first in the glass phase and then in the crystals.

[0068] The glass phase of the high crystallinity microcrystalline glass of the present invention is particularly small, and there is a rare glass phase. Even if ion exchange occurs, there are very few ions that enter the glass phase, so the ability to change the structure and coordination of Si-O in the glass phase is very low and local, so the impact on the formation of the valence bond of the coating described in the present invention is very small, that is, whether high crystallinity glass is ion-exchanged or not, its interface always lacks Si-O structure, and the present invention is an invention made for such an application scene, and when high temperature is used, the ions in the crystal participate in ion exchange, that is, the crystal is destroyed, so the Si-O in the crystal opens and only contributes to the formation of the valence bond of the coating described in the present invention. What the present invention aims to solve is how to form a strong, durable, and excellent water-repellent and oil-repellent coating film when there are very few Si-O structures at the interface of the coating film, and high crystallinity glass, whether ion-exchanged or not, is not so hard that it affects the implementation of the present invention.

[0069] The method for producing the microcrystalline glass or glass ceramics containing a water- and oil-repellent composite coating layer on the surface thereof according to the present invention will be specifically described below.

[0070] The composition components are 40 to 75%, preferably 45 to 72% SiO2; 2 to 20%, preferably 4 to 15% Al2O3; 0 to 20%, preferably 0.4 to 1.6%, of B2O3; 0 to 10%, preferably 0.8 to 1.5%, of P2O5; 0-15%, preferably 0.9-4% ZrO2+TiO2; 0 to 5%, preferably 0.1 to 2% MgO; 0 to 4%, preferably 0.9 to 3.0% ZnO; 0 to 5%, preferably 0.01 to 1%, of rare earth oxides; 0-5.5% Na2O, 0-4% K2O, 2 to 34%, preferably 10 to 34%, LiO; A glass containing 4 to 40%, preferably 15 to 40%, Na2O+K2O+Li2O is fired by the following method to obtain a microcrystalline glass or glass ceramics.

[0071] Here, the microcrystalline glass or glass ceramic is Step (I) of melting each glass raw material at a high temperature of 1600±50°C and then annealing it at 400-650°C to obtain a homogenized raw glass plate; (II) obtaining a shaped raw glass plate from the raw glass plate by an overflow downdraw method, a float method or a rolling method; Step (III) of microcrystallizing the raw glass plate by two heat treatments to obtain a microcrystalline glass preform, in which the first heat treatment is performed at a temperature of 500 to 1000°C for 0.5 to 5 hours, and the second heat treatment is performed at a temperature of 550 to 1100°C for 0.5 to 6 hours; The microcrystalline glass preform is obtained by firing it in a method including a step (IV) in which the microcrystalline glass preform is either ion-exchanged or not, and is used to coat the required undercoat layer, intermediate layer and water- and oil-repellent layer on the surface in that order.

[0072] Here, the ion exchange may be carried out by a conventional method. For example, the ion exchange may be carried out for 5 to 10 hours within a temperature range of 380 to 500°C using a mixed molten salt containing, on a mass basis, 10 to 75 wt% NaNO3 and 25 to 90 wt% KNO3.

[0073] Specifically, the firing method includes the steps of first weighing glass raw materials and melting them at a high temperature such as 1600±50°C, then annealing them at about 400°C to 650°C, and then homogenizing the glass to form a microcrystalline glass substrate. The microcrystalline glass substrate is also called a raw glass plate, which is a glass plate that has not yet been subjected to crystallization treatment, and does not contain crystals. Depending on its high-temperature viscosity and material properties, it can be formed using methods such as overflow downdraw method, float method, and rolling method, and the thickness of the obtained raw glass plate is between 0.1 to 5 mm. Furthermore, it can be formed into a block shape, annealed, and then cut into a plate shape.

[0074] After the microcrystalline glass substrate is formed, the microcrystalline glass substrate is heat-treated twice to microcrystallize it, and a microcrystalline glass preform can be manufactured, where the first heat treatment is performed at a temperature of about 500 to 1000°C for 0.5 to 5 hours, and the second heat treatment is performed at a temperature of about 550 to 1100°C for 0.5 to 6 hours. After crystallization, the required microcrystalline glass or glass ceramic is formed, and then it is put into a vacuum coating machine PVD after ion exchange or without ion exchange, and the coating parameters are set, and the undercoat layer, intermediate layer, and water- and oil-repellent layer are coated in this order. The flow in the vacuum coating machine is glass loading-vacuum drawing-plasma cleaning-deposition-air release (from vacuum to atmospheric pressure)-unloading.

[0075] Hereinafter, the production of the chemically strengthened glass of the present invention and the stress performance characteristics of the chemically strengthened glass of the present invention will be described in detail with reference to examples.

[0076] [First Part: Glass Manufacturing Example] Taking Example 1 as an example, how to manufacture a glass substrate will be described.

[0077] (1) The materials of Example 1 shown in Table 1 are mixed, the mixed material is placed in a platinum crucible, and melted for 5 hours while keeping the temperature at 1600 ° C in an elevation type high temperature furnace, and then poured into a preheated stainless steel mold, placed in an annealing furnace, and annealed for 24 hours while keeping the temperature at 580 ° C to remove the internal stress of the glass. After the annealing is completed, the glass block is cut with excess parts on six sides to obtain a glass block, and then cut to exact size, surface grinded, and edge swept using a wire cutter, a CNC engraving machine, a surface grinder, and a buff polisher to obtain a raw glass plate with a size of 155 mm × 78 mm × 0.65 mm.

[0078] Here, the explanation of the model numbers of the equipment used in the above process is as follows: Multi-wire cutting machine: CH5625, Taizhou Chenhong CNC Equipment Manufacturing Co., Ltd. CNC machine tool carving machine: CN-650, Shandong Chinuo CNC Equipment Co., Ltd. Surface grinding machine: YJ-13B6LD, Hunan Ningjing Machinery Co., Ltd., and Buffing machine: YJ-13B6PD, Hunan Ningjing Machinery Co., Ltd.

[0079] (2) First, in an elevating high-temperature furnace, the raw glass plate is subjected to a first heat treatment at 650°C for 3 hours to form crystal nuclei, and then a second heat treatment is performed at 730°C for 3 hours to precipitate crystals, thereby producing glass ceramics. The glass ceramics are subjected to crystallization analysis including the degree of crystallization, the crystal type (main crystal phase and sub crystal phase type), the ratio of the main crystal phase and the sub crystal phase, and the average crystal grain size, and the Vickers hardness, fracture toughness, average visible light transmittance, and haze of the glass ceramics (hereinafter also referred to as "non-ion-exchanged glass ceramics").

[0080] (3) Ion exchange is performed on the glass ceramics. A mixed salt bath of 40 wt% NaNO3 and 60 wt% KNO3 is used as the molten salt. The tempering temperature (i.e., ion exchange temperature) is 380°C, and the tempering time is 9 hours. After tempering is completed, the glass ceramics are removed and washed to obtain tempered glass ceramics (hereinafter also referred to as "glass ceramics that have undergone ion exchange").

[0081] (4) The obtained tempered glass-ceramics are subjected to the corresponding characteristic tests, including haze, average visible light transmittance, surface compressive stress, compressive stress depth and Young's modulus, and the specific test results are shown in Table 3.

[0082] Here, the definitions and test methods of the crystallinity, main crystalline phase, sub crystalline phase, average crystal grain size, Vickers hardness, fracture toughness, average visible light transmittance, haze, surface compressive stress, compressive stress depth and Young's modulus will be specifically described as follows.

[0083] The surface compressive stress here means that after the glass is chemically strengthened, alkali metal ions with small radii are replaced by alkali metal ions with large radii on the surface, and compressive stress is generated on the glass surface due to the crowding effect of the alkali metal ions with large radii, which is called surface compressive stress.

[0084] Crystallinity: The diffraction peak curve is obtained by analysis of XRD diffraction instrument, where the range of incident angle is 2Theta=10-50 degrees, the scanning speed is 6 degrees / min, and the instrument used in this embodiment is Shimadzu XRD-6000. The crystallinity is calculated by the formula (1-1):

number

[0085] Proportion of the main crystalline phase: In a glass-ceramic, the crystalline phase that has the highest proportion, by mass, relative to other crystalline phases.

[0086] Proportion of minor crystalline phase: Besides the main crystalline phase, one or more other crystalline phases may further be present in the ceramic portion of the glass-ceramic, and the weight percentage of the minor crystalline phase is smaller than the weight percentage of the main crystalline phase.

[0087] Average crystal grain size: The average length of the crystal grains of the microcrystalline glass observed at a magnification of 100,000 to 1,000,000 times. Obtained by observation with a transmission electron microscope (model number: Thermo Fisher Scientific (formerly FEI) Talos F200S). During measurement, an enlarged photograph is taken of the crystal grains of a certain area, and there are finite crystal grains in the enlarged photograph area. The size of the finite crystal grains is marked on a reduced scale, and then the average value is calculated. In the embodiment of the present invention, the magnification during measurement is 500,000 times.

[0088] Vickers hardness: A Vickers hardness tester is used to test the Vickers hardness, which is tested according to the standard "GB / T 37900-2019 Ultra-thin Glass Hardness and Fracture Toughness Test Method: Low-load Vickers Hardness Indentation Method". The instrument used in this embodiment is a digital display low-load Vickers hardness tester VTD405 (Beijing Wowwei Technology Co., Ltd.).

[0089] Fracture toughness: represents the result of indentation measurement. After the test sample is polished, the diamond indenter of the Vickers hardness tester is used to press the sample with a load p of 300N for 10 seconds to make an indentation, whereby a corresponding crack is generated at the apex of the indentation, and the fracture toughness value K is calculated based on the indentation load P and the length of the crack extension C. ICThe specific fracture toughness is obtained by testing and calculating according to the standard "GB / T 37900-2019 Ultra-thin glass hardness and fracture toughness test method: small load Vickers hardness indentation method".

[0090] Surface compressive stress (MPa): A waveguide optical stress meter FSM-6000LE manufactured by ORIHARA Co., Ltd., Japan is used to test the surface compressive stress of the glass to be measured.

[0091] Depth of compressive stress (μm): The distance from the surface of the glass being measured to the point where the compressive stress is zero.

[0092] Haze: The percentage of transmitted light intensity that deviates from the incident light by 2.5° or more out of the total transmitted light intensity, measured using a colorimeter (model number CM~3600A).

[0093] Visible light transmittance: Within the wavelength range of visible light, it is the ratio of the radiant energy projected onto an object and transmitted through it as the incident light flux leaves the incident surface of the irradiated surface or medium and exits the other surface, to the total radiant energy projected onto the object.

[0094] Visible light average transmittance: A value obtained by measuring the transmittance at each wavelength at 10 nm intervals within a specific wavelength range, and dividing the sum of the measured transmittances at each wavelength by the number of measured transmittances at each wavelength. For example, the method of calculating the average transmittance at a wavelength of 360 to 400 nm is to measure the transmittances at wavelengths of 360 nm, 370 nm, 380 nm, 390 nm, and 400 nm, respectively, and the number of measured 360 to 400 nm transmittances is 5, and the sum of the transmittances is divided by 5 to obtain the average transmittance at a wavelength of 360 to 400 nm.

[0095] Young's modulus (Gpa): The Young's modulus of the sample is obtained by testing using the sonic method, and the equipment used is the IET-1600P high temperature elastic modulus tester.

[0096] [Examples 2 to 13] The steps of the manufacturing method are the same as those in Example 1, and the details of the differences can be seen in Tables 1, 2 and 3, that is, the composition components of each raw material in the specific glass recipe, the heat treatment process conditions in step (2), the performance test results of the obtained glass ceramics, and the ion exchange process conditions in step (3) and the performance test results of the obtained tempered glass ceramics are shown in Tables 1, 2 and 3.

[0097] [Table 1]

[0098] [Table 2-1] [Table 2-2] [Table 2-3] [Table 2-4] [Table 2-5]

[0099] As can be seen from Table 2 above, the crystallinity of the glass ceramic obtained by heat treating the raw glass obtained in the present invention is at least 61.2% and at most 90.35%, the visible light transmittance is between 89 and 92%, the average crystal grain size is between 15.7 nm and 25.5 nm, the haze is 0.09 to 0.20%, the Vickers hardness is 718 to 796 HV, and the fracture toughness is 1.4 to 1.9 MPa m 1 / 2 It is.

[0100] [Table 3-1]

[0101] As can be seen from the above glass composition, the glass recipe may contain rare earth oxides. Specifically, the present invention may contain one or more of CeO2, Y2O3, La2O3, Ta2O3, Tm2O5, and Nb2O5. The content of these rare earth oxides usually does not exceed 5 mol%. In addition, colorants and clarifiers may be added as necessary. Specifically, in the above glass composition, Nb2O3 acts as a colorant, and in the present invention, in addition to Nb2O3, Nd2O3 is also added. , Fe2O3, CoO, NiO, V2O5, MnO2, TiO2, CuO, CeO2 and Cr2O3 may be added as colorants. After adding the colorants, the visible light transmittance of the glass decreases, and the more colorants added, the lower the transmittance. In general, the addition ratio does not exceed 5 mol%, and adding 1 mol% or more will cause a significant change in the color and transmittance of the entire glass. Adding too much colorant (for example, about 5 mol%) will affect the crystallinity and crystal size of the microcrystalline glass. In the present invention, in addition to all the components in the above examples, by adding 1 mol% of any combination of Fe2O3, NiO, MnO2 and other colorants in any ratio, the glass will exhibit a black color, and by adding 0.5 mol% or more of any combination of CoO, Cr2O3 and other colorants in any ratio, the glass will exhibit a black color with a blue phase. If the colorants used do not exceed 5 mol%, other performance properties of the glass will not be affected.

[0102] In the glass of the present invention, the fining agents may be used alone or in combination according to the actual melting conditions. The fining agents include As2O3, Sb2O3, SnO2, and SO3. - The fining agent is one or more selected from the group consisting of compounds of As2O3, fluorides or salts, chlorides or salts, and nitrates. Here, As2O3 and Sb2O3 have a very good fining effect as a fining agent, but are not preferred due to their certain toxicity. Fluorides can also be used as a fining agent, but are not preferred due to their corrosiveness. Usually, SnO2, SO3 (e.g., Na2SO4), Cl compounds (e.g., NaCl), and NO3 -A single substance or combination of compounds (eg, NaNO3) are conventional fining agents, generally not exceeding 1 mol%.

[0103] [Example of the second part: Example of the preparation of a water- and oil-repellent composite coating layer] 1. Composite coating layers are formed using the non-ion-exchanged glass ceramics and the ion-exchanged glass ceramics of Example 4 as glass substrates. The raw glass obtained in Example 4 of the first part, i.e., the glass ceramic lot not subjected to the ion exchange treatment in step (3) (numbered respectively as #4-A1 to 4-A15), and the ion-exchanged glass ceramics (i.e., subjected to the ion exchange treatment in step (3)) are used as the glass substrates (numbered respectively as #4-B1 to 4-B15), to form a composite coating layer containing the SiO2, NaF and AF film, and the non-ion-exchanged glass ceramics (numbered respectively as #4-A16 to 4-A18) and the ion-exchanged glass ceramics (numbered respectively as #4-B16 to 4-B18), to form only a composite coating layer containing the SiO2 and AF film, respectively. Specifically, a composite coating layer is formed by using the vacuum coating equipment shown in Table 4-1 and the coating conditions shown in Table 4-2 (Note: In each embodiment, the coating time is controlled according to the target coating layer thickness, and coating is stopped when the target thickness is reached), and according to the following method, the glass substrate surface is respectively cleaned by ultrasonic cleaning (can be cleaned by flat brush), and after the surface of the glass substrate is cleaned, each essentially uniform film layer is formed on the substrate surface in sequence by using a vacuum coating method, where the vacuum coating process is performed by placing the glass sample to be coated on an umbrella-shaped coating rack, then inserting the umbrella-shaped coating rack into a table work holder, and separately inserting the SiO2 and NaF coating materials into the two electron gun crucibles of the vacuum coating machine (using Hanil Vacuum 2050 type electron gun vacuum coating machine) without mixing them, filling the crucibles with the materials and making them flat with the surface of the crucible mouth, and then forming an AF film (Anti-Fingerprint Film (AF Film)) into an evaporation prevention molybdenum boat. Put the AF film material (600ml of AF liquid is dropped into the crucible containing steel wool, and the crucible after the AF liquid dries is called the AF film material) to form the anti-fingerprint film (Glass), close the vacuum chamber, start evacuation, and when the bottom vacuum reaches the vacuum level specified in Table 4-2 of the setting process, automatically flow Ar gas at a rate of 28sccm into the device, and use Hanil's own Ion BeamThe hole ion source is operated to perform ion bombardment and cleaning of the surface of the sensitized glass, and then, as shown in Table 4-2, specific conditions such as the degree of vacuum in the process, ion source voltage, ion source current, neutralization current, Ar and O2 gas ratio, electron gun operating current, film formation speed, and coating thickness (here, before coating, when performing plasma cleaning, the coating time parameters are controlled and adjusted) are controlled, and SiO2 and NaF (the raw materials SiO2 and NaF used are both particulate) are coated in turn according to these conditions, and then, as shown in Table 4-2, specific conditions such as the degree of vacuum in the process, deposition prevention operating current, film formation speed, and coating thickness are controlled, and AF is coated according to these conditions, and here, L5 type SiO2 from Merck, Germany is used as the coating material for the SiO2 film.

[0104] The NaF film is made of NaF provided by Nanyang Yingfukang Photoelectric Materials Co., Ltd. as a coating material, and the AF film (Anti-Fingerprint Glass) is made of KyY1905-1 type fluorine-containing polyether manufactured by Shin-Etsu Chemical Co., Ltd. of Japan as a coating material with AF base material (manufactured by Shin-Etsu Chemical Co., Ltd.) (abbreviated as "PFPE" film).

[0105] After the coating was completed, contact angle tests were performed on the outer surfaces of the non-ion-exchanged glass ceramics and the ion-exchanged glass ceramics. The thicknesses of the SiO2, NaF and AF film layers and the contact angle test results for the film layers are shown in Tables 5-1 and 5-2.

[0106] After coating, the water contact angle, oleic acid contact angle and water drop angle after abrasion of the coating surface are measured to discuss the coating quality and durability.

[0107] Here, the water contact angle (°) of the AF film surface is measured using a method based on JIS R 3257 (1999).

[0108] Here, the method for measuring the contact angle of oleic acid on the AF film surface is to drop 7 μL of liquid onto a horizontal coating film sample and measure the cut angle.

[0109] Using hexadecane instead of water, the contact angle of oleic acid was tested by dropping it onto the non-ion-exchanged glass ceramics. The test results for the glass ceramics with numbers #4-A10, #4-A11, and #4-A12 are as follows: [Table 3-2]

[0110] Abrasion resistance test: 1cm 2 A Korean minoan solid eraser (diameter 6 mm, A type) (manufactured by MIRAE SCIENCE, minoan) was used as an abrasion-resistant indenter, and the AF film surface formed on the surface of the glass substrate was rubbed back and forth 2500 (or more) times under the conditions of a stroke width of 40 mm and a speed of 40 mm / sec under a load of 1 kgf, followed by dry wiping with a cloth [Ozu Sangyo Co., Ltd., DUSPER (registered trademark)] to clean the AF film surface. After the abrasion resistance test of the AF film, the water contact angle (°) was measured at three positions on the surface, and each position was measured three times, and the average water contact angle (°) at a total of nine positions was measured.

[0111] [Table 4-1] Note: Coating is performed to form the vacuum condition as required, and those skilled in the art can select some or all of the pumps listed in Table 4-1 above according to conventional means and use them as needed. Here, the mechanical pump is also called a back pump, which uses oil to maintain the sealing effect and continuously changes the volume of the suction cavity in the pump by mechanical means, so that the volume of the gas in the sucked container continues to expand, resulting in a vacuum; the Roots pump is a booster pump, which functions to increase the pressure difference between the intake port and the exhaust port, and it uses a mechanical pump as a back pump; the diffusion pump is a pump used to obtain a high vacuum, and when using the diffusion pump, a mechanical pump and a Roots pump are used as back pumps; Polycold is a low-temperature water gas pump, which is used to capture residual gases present in the high vacuum environment using the diffusion pump; the working principle is to place a refrigeration coil that can reach -120℃ or lower at the pump port of the diffusion pump, and the low-temperature condensation effect on its surface is used to quickly capture the residual gases in the vacuum system.

[0112] [Table 4-2]

[0113] [Table 5-1]

[0114] [Table 5-2]

[0115] 2. Form a composite coating layer using the non-ion-exchanged glass ceramics and the ion-exchanged glass ceramics in Example 8 as glass substrates.

[0116] The procedure is similar to that of forming a composite coating layer using the glass ceramics formed in Example 4 of Section 1 as the glass substrate, but the difference is that in this section, the non-ion-exchanged glass ceramics (numbered #8-A1 to #8-A15, respectively) and the ion-exchanged glass ceramics (numbered #8-B1 to #8-B15, respectively) in Example 8 are used as the glass substrate to form a composite coating layer containing SiO2, NaF and AF film, and a composite coating layer containing only SiO2 and AF film (the numbers of the non-ion-exchanged glass ceramics are #8-A16 to #8-A18, respectively, and the numbers of the ion-exchanged glass ceramics are #8-B16 to #8-B18, respectively). The water contact angle test results of the outer surface of the coating layer are shown in Tables 6-1 and 6-2.

[0117] [Table 6-1]

[0118] [Table 6-2]

[0119] 3. Form a composite coating layer using the non-ion-exchanged glass ceramics and the ion-exchanged glass ceramics in Example 12 as glass substrates. The procedure is similar to that of forming a composite coating layer using the glass-ceramics formed in Example 4 of Section 1 as the glass substrate, but the difference is that in this section, the non-ion-exchanged glass-ceramics (numbered #12-A1 to #12-A15) and the ion-exchanged glass-ceramics (numbered #12-B1 to #12-B15) in Example 12 are used as the glass substrate to form a composite coating layer containing SiO2, NaF and AF film, and a composite coating layer containing only SiO2 and AF film (the numbers of the non-ion-exchanged glass-ceramics are #12-A16 to #12-A18, and the numbers of the ion-exchanged glass-ceramics are #12-B16 to #12-B18). The water contact angle test results of the outer surfaces of the coating layers are shown in Tables 7-1 and 7-2.

[0120] [Table 7-1]

[0121] [Table 7-2]

[0122] 4. Form a composite coating layer using the non-ion-exchanged glass ceramics and the ion-exchanged glass ceramics in Example 13 as glass substrates. The operation is similar to that of forming a composite coating layer using the glass ceramics formed in Example 4 of Section 1 as the glass substrate, but the difference is that in this section, the non-ion-exchanged glass ceramics (numbered #13-A1 to #13-A15) and the ion-exchanged glass ceramics (numbered #13-B1 to #13-B15) in Example 13 are used as the glass substrate to form a composite coating layer containing SiO2, NaF and AF film, and a composite coating layer containing only SiO2 and AF film (the numbers of the non-ion-exchanged glass ceramics are #13-A16 to #13-A18, and the numbers of the ion-exchanged glass ceramics are #13-B16 to #13-B18). The water contact angle test results of the outer surface of the coating layer are shown in Tables 8-1 and 8-2.

[0123] [Table 8-1]

[0124] [Table 8-2]

[0125] As can be seen from the experimental results in Tables 5-1, 5-2, 6-1, 6-2, 7-1, 7-2, 8-1 and 8-2 above, four glass ceramics with different crystal ratios were selected from 13 glass ceramic recipes, and three coating layers were formed using the non-ion-exchanged and ion-exchanged glass substrates, respectively. Based on these data, the following conclusions can be drawn.

[0126] 1) If the thickness of the undercoat layer is too thick and exceeds 20 nm, the abrasion resistance of the AF is poor, so the thickness should preferably not exceed 15 nm.

[0127] 2) When the intermediate layer is too thick, exceeding 5 nm, the AF has poor initial performance and wear resistance. However, when there is no intermediate layer, as can be seen from the contact angle data in the last three rows of each table, the initial contact angle is mostly less than 100 degrees, but the contact angle after 2,500 frictions reaches a maximum of about 60 degrees.

[0128] 3) The primer layer is adequate, the intermediate layer is thin, and the AF layer is either thick or thin, and both are effective.

[0129] 4) The surface layer is 10 nm or more, and the resulting composite coating layer has good water- and oil-repellency and excellent abrasion resistance. It is preferable that the surface layer is 15 nm or more. The thicker the surface layer, the higher the abrasion resistance. From the viewpoint of cost, the surface layer should not exceed 25 nm, so that the resulting coating layer has ideal water- and oil-repellency and abrasion resistance.

[0130] 5) Even if the three-layer composite coating layer is directly formed on the glass ceramics without ion exchange, i.e., prestressing treatment, the water and oil repellency is excellent. When the three-layer composite coating layer is formed on the ion-exchanged tempered glass, the abrasion resistance test results show that the contact angle is larger, that is, the water and oil repellency effect is better.

[0131] In summary, the thickness of the undercoat layer is preferably 3 to 15 nm, the thickness of the intermediate layer is 1 to 5 nm, the thickness of the AF film layer is 10 nm or more, preferably 15 nm or more, and may be in the range of 10 to 25 nm, and the thickness of the intermediate layer is preferably 1 to 2 nm, and it is effective if the undercoat layer is formed to a thickness of 5 to 10 nm, and 5 to 8 nm is optimal.

[0132] 5. For the non-ion-exchanged glass ceramics in Example 4 of the first part (based on the 4# recipe, glass ceramics are manufactured according to the above steps (1) and (2), and the ion-exchange treatment of step (3) is not performed), composite coating layers (numbered #4-a1, #4-a2, and #4-a3, respectively) are formed on the surface according to the operating method and conditions described in Section 1 above, the only difference being that the thicknesses of each coating layer are different, as shown in Table 9 below. The coating quality and durability of the composite coating film formed on the surface were tested, and the results are summarized in Table 9 below.

[0133] For the ion-exchanged glass ceramics in Example 4 of Part 1, a composite coating layer (also called tempered glass, numbered #4-b1, #4-b2, #4-b3 respectively) was formed on the surface according to the operating method and conditions described in Section 1 above, the only difference being that the thicknesses of each coating layer are different, as shown in Table 9 below. The coating quality and durability performance of the composite coating film formed on the surface were tested, and the surface compressive stress and compressive stress depth were tested according to the test method in Example 4 of Part 1. All the test results are summarized in Table 9 below.

[0134] The non-ion-exchanged glass ceramics in Example 4 of the first part were mixed with black colorants, that is, based on the 4# recipe, 0.5 mol% NiO, 1 mol% Fe2O3, and 0.3 mol% CoO were added based on the molar sum of each substance in the original raw glass recipe, and glass ceramics were produced according to steps (1) and (2) in the "Example of Glass Production" of the first part, and composite coating layers (also called non-ion-exchanged black glass or non-prestressed black glass, numbered #4-c1, #4-c2, and #4-c3, respectively) were formed on the surface according to the operating method and operating conditions described in Section 1 above, with the only difference being that the thicknesses of each coating layer were different, as shown in Table 9 below. The coating quality and durability of the composite coating film formed on the surface were tested, and the results were summarized in Table 9 below. The black glass obtained has an opaque black appearance, and when irradiated with strong white light, it shows a deep blue-black color.

[0135] [Table 9]

[0136] As can be seen from Table 9 above, the intermediate layer is thin, within the range of 1 to 3 nm, and regardless of whether it is ion-exchanged, i.e., glass prestressed, the AF film on the outer surface of the obtained composite coating layer has both excellent bonding strength and wear resistance, and even after adding a black colorant, the bonding strength and wear resistance of the AF film are not affected.

[0137] (Additional Note) (Appendix 1) A microcrystalline glass containing a water- and oil-repellent composite coating layer on its surface, the microcrystalline glass including, in order from the outermost surface, a water- and oil-repellent layer, an intermediate layer, and an undercoat layer, the intermediate layer being an ion crystal intermediate layer having a crystal lattice energy of 700 to 3000 kJ / mol, and the undercoat layer including a compound containing Si-O bonds or a mixed silicon oxide layer; A microcrystalline glass characterized by:

[0138] (Appendix 2) The crystallinity may be greater than 60%, or greater than 70%, or greater than 80%. The microcrystalline glass described in Appendix 1.

[0139] (Appendix 3) The intermediate layer is an intermediate layer formed from an ionic crystal having a crystal lattice energy of 725 to 3000 kJ / mol, more preferably 770 to 3000 kJ / mol, as the original coating film material. Or, a fluoride intermediate layer formed using a compound having a crystal lattice energy of 9400 to 11400 KJ / mol, preferably a silicofluoride, as the original coating film material. The microcrystalline glass according to claim 1 or 2.

[0140] (Appendix 4) The intermediate layer contains an alkali metal fluoride or an alkaline earth metal fluoride compound, or is an intermediate layer formed using ion crystals selected from alkali metal silicofluorides and alkaline earth metal silicofluorides as the original coating film material. The microcrystalline glass according to appendix 3.

[0141] (Appendix 5) The intermediate layer is an ionic crystalline intermediate layer having a crystal lattice energy of less than 1050 KJ / mol, preferably less than 940 kJ / mol; The microcrystalline glass according to any one of claims 1 to 3.

[0142] (Appendix 6) The intermediate layer is a crystal formed using at least one ion crystal of LiF, NaF and / or KF as an original coating film material, or an intermediate layer formed using at least one of MgF2, CaF2, SrF2 or BaF2 as an original coating film material, or a fluoride intermediate layer formed using at least one of Li2SiF6, Na2SiF6, K2SiF6, Rb2SiF6, Cs2SiF6, BeSiF6, MgSiF6, CaSiF6, SrSiF6 or BaSiF6 as an original coating film material, The intermediate layer is preferably formed using NaF or KF ion crystals as the original coating material. The microcrystalline glass according to claim 5.

[0143] (Appendix 7) the thickness of the intermediate layer is between 1 and 5 nm, preferably between 1 and 2 nm; and / or The thickness of the undercoat layer is from 3 to 15 nm, preferably from 5 to 10 nm, and more preferably from 5 to 8 nm; and / or The thickness of the water- and oil-repellent layer is 10 nm or more, preferably 15 nm or more, and may be 10 nm to 25 nm. The microcrystalline glass according to any one of claims 1 to 6.

[0144] (Appendix 8) When the undercoat layer is a multi-layered layer, the compound containing Si-O bonds or the mixed silicon oxide layer is the outermost undercoat layer, and the mixed silicon oxide is silicon oxide SiO x (x is 2 or less) and at least one oxide of an element other than silicon and / or magnesium fluoride; The other element is preferably an element selected from the group consisting of aluminum, tin, magnesium, phosphorus, cerium, zirconium, titanium, cesium, barium, strontium, niobium, zinc, and boron, and the mixed silicon oxide is preferably a silicon oxide SiO x and an oxide of aluminum, The compound containing the Si-O bond is preferably SiOx (x is 2 or less), or any one of SiOC, SiON, SiOCN and / or Si3N4, or a hydrogen bond bonded to any one of SiOx (x is 2 or less), SiOC, SiON and / or SiOCN in any ratio. The microcrystalline glass according to any one of claims 1 to 7.

[0145] (Appendix 9) The water- and oil-repellent layer is a fluorine-based polymer layer, and is preferably a fluorine-containing polyether silicon oxide layer having a molecular weight of 2000 or more. The microcrystalline glass according to any one of claims 1 to 8.

[0146] (Appendix 10) The composition of the microcrystalline glass is the following oxides in mol% ratio: 40 to 75%, preferably 45 to 72% SiO2; 2 to 20%, preferably 4 to 15% Al2O3; 0 to 20%, preferably 0.4 to 1.6%, of B2O3; 0 to 10%, preferably 0.8 to 1.5%, of P2O5; 0-15%, preferably 0.9-4% ZrO2+TiO2; 0 to 5%, preferably 0.1 to 2% MgO; 0 to 4%, preferably 0.9 to 3.0% ZnO; 0 to 5%, preferably 0.01 to 1%, of rare earth oxides; 0-5.5% Na2O, 0-4% K2O, 2 to 34%, preferably 10 to 34%, LiO; Contains 4 to 40%, preferably 15 to 40%, Na2O+K2O+Li2O, The microcrystalline glass may be ion-exchanged or non-ion-exchanged glass. The microcrystalline glass according to any one of claims 1 to 9.

[0147] (Appendix 11) The rare earth oxide is one or more selected from CeO2, Y2O3, La2O3, Ta2O3, Tm2O5, and Nd2O5; 11. The microcrystalline glass according to claim 10.

[0148] (Appendix 12) The microcrystalline glass may further contain a color additive and / or a fining agent, the color additive being preferably one or more selected from Nd2O3, Fe2O3, CoO, NiO, V2O5, MnO2, TiO2, CuO and Cr2O3, the molar content of the color additive relative to the total components of the glass being more preferably not more than 5%, and the color additive preferably contains 0.5 mol% or more of CoO and / or Cr2O3, and more preferably contains 1 mol% or more of one or more selected from Fe2O3, NiO or MnO2, in terms of the molar content relative to the total components of the glass, and / or The fining agent is As2O3, Sb2O3, SnO2, chloride, fluoride, SO3 - Containing compounds and NO3 - It is preferable that the compound is one or more selected from the group consisting of SnO2, SO3 - Containing compounds, chlorides, and NO3 - It is more preferable that the content of the clarifier is one or more selected from the group consisting of 0 to 2 mol%. The microcrystalline glass according to any one of claims 1 to 11.

[0149] (Appendix 13) The main crystal phase of the microcrystalline glass is one or more selected from β-quartz solid solution, β-spodumene solid solution, β-eucryptite, spinel, rutile, mullite, olivine, enstatite, cordierite, petalite, lithium silicate, lithium disilicate, quartz, zirconia, and magnetite, and the average crystal grain size is preferably less than 100 nm, more preferably 50 nm or less, and particularly preferably 30 nm or less. The microcrystalline glass according to any one of claims 1 to 12.

[0150] (Appendix 14) Step 1) of coating the microcrystalline glass with a Si-O containing oxide or mixed silicon oxide layer to form a primer layer on the surface of the microcrystalline glass; Step 2) of coating an intermediate layer on the surface of the undercoat layer obtained in step 1); Step 3) of coating a water- and oil-repellent layer on the surface of the intermediate layer obtained in step 2), It is preferable that the coating is performed by a vacuum deposition method. A method for producing microcrystalline glass according to any one of claims 1 to 13.

[0151] (Appendix 15) The microcrystalline glass is, before coating the undercoat layer, the intermediate layer, and the water- and oil-repellent layer, Step (I) of melting each glass raw material at a high temperature of 1600±50°C and then annealing it at 400-650°C to obtain a homogenized raw glass plate; (II) obtaining a shaped raw glass plate from the raw glass plate by an overflow downdraw method, a float method or a rolling method; and step (III) of microcrystallizing the raw glass plate by two heat treatments to obtain a microcrystallized glass preform, which is then either ion-exchanged or not ion-exchanged and used as a raw material for microcrystallized glass to coat the required undercoat layer, intermediate layer and water- and oil-repellent layer on the surface in that order, with the proviso that the first heat treatment temperature is 500-1000°C and the second heat treatment temperature is 550-1100°C. The manufacturing method described in Appendix 14.

Claims

1. A microcrystalline glass containing a water- and oil-repellent composite coating layer on its surface, the microcrystalline glass comprising, in order from the outermost surface, a water- and oil-repellent layer, an intermediate layer, and an undercoat layer, the intermediate layer being an ion crystal intermediate layer containing a crystal lattice energy of 700 to 3000 kJ / mol, the undercoat layer containing a compound containing Si-O bonds or a mixed silicon oxide layer, and the microcrystalline glass further containing a coloring additive; The color additive is one or more selected from Nd2O3, Fe2O3, CoO, NiO, V2O5, MnO2, TiO2, CuO and Cr2O3; A microcrystalline glass characterized by:

2. The molar content of said color additive relative to the total composition of the glass does not exceed 5%; The microcrystalline glass according to claim 1 .

3. The crystallinity is greater than 60%, or greater than 70%, or greater than 80%. The microcrystalline glass according to claim 1 or 2.

4. The microcrystalline glass is a black glass. The microcrystalline glass according to claim 1 or 2.

5. The intermediate layer is an intermediate layer formed from an ion crystal having a crystal lattice energy of 725 to 3000 kJ / mol as a coating material, Or, the intermediate layer is a fluoride layer formed using a silicofluoride having a crystal lattice energy of 9400 to 11400 KJ / mol as the original coating film material. The microcrystalline glass according to any one of claims 1 to 4.

6. The intermediate layer is an intermediate layer formed from an ionic crystal having a crystal lattice energy of 770 to 3000 kJ / mol as the original coating film material. The microcrystalline glass according to claim 5.

7. The intermediate layer contains an alkali metal fluoride or an alkaline earth metal fluoride compound, or is an intermediate layer formed using ion crystals selected from alkali metal silicofluorides and alkaline earth metal silicofluorides as the original coating film material. The microcrystalline glass according to claim 5 or 6.

8. The intermediate layer is an ionic crystal intermediate layer having a crystal lattice energy of less than 1050 KJ / mol. The microcrystalline glass according to any one of claims 1 to 5.

9. The intermediate layer is a crystal formed from at least one of LiF, NaF and / or KF ion crystals as the original coating material, or MgF 2 , CaF 2 , SrF 2 or BaF 2 or Li 2 SiF 6 , Na 2 SiF 6 , K 2 SiF 6 , Rb 2 SiF 6 , Cs 2 SiF 6 , BeSiF 6 , MgSiF 6 , CaSiF 6 , SrSiF 6 , or BaSiF 6 The fluoride intermediate layer is formed using at least one of the following as the original coating film material: The microcrystalline glass according to claim 7 or 8.

10. The thickness of the intermediate layer is 1 to 5 nm, and / or the thickness of the undercoat layer is 3 to 15 nm; And / or, the thickness of the water- and oil-repellent layer is 10 nm or more; The microcrystalline glass according to any one of claims 1 to 9.

11. The intermediate layer has a thickness of 1 to 2 nm, and / or the thickness of the undercoat layer is 5 to 10 nm; And / or, the thickness of the water- and oil-repellent layer is 15 nm or more; The microcrystalline glass according to claim 10.

12. The thickness of the water- and oil-repellent layer is 10 nm to 25 nm. The microcrystalline glass according to any one of claims 1 to 11.

13. When the undercoat layer is a multi-layered layer, the compound or mixed silicon oxide layer containing Si—O bonds is used as the outermost undercoat layer, and the mixed silicon oxide is silicon oxide SiO x and at least one oxide of an element other than silicon and / or magnesium fluoride, where x is 2 or less; The microcrystalline glass according to any one of claims 1 to 12.

14. the other element is an element selected from the group consisting of aluminum, tin, magnesium, phosphorus, cerium, zirconium, titanium, cesium, barium, strontium, niobium, zinc, and boron; The compound containing a Si-O bond is SiOx, or SiOC, SiON, SiOCN and / or Si 3 N 4 or any one of SiOx, SiOC, SiON and / or SiOCN in any ratio, where x is 2 or less; The microcrystalline glass according to claim 13.

15. The water- and oil-repellent layer is a fluorine-based polymer layer. The microcrystalline glass according to claim 14.

16. The water- and oil-repellent layer is a fluorine-containing polyether silicon oxide layer having a molecular weight of 2000 or more. The microcrystalline glass according to claim 15.

17. The composition of the microcrystalline glass is the following oxides in mol % ratio: 40-75% SiO 2 and, 2-20% Al 2 O 3 and, 0-20% B 2 O 3 and, 0-10% P 2 O 5 and, 0-15% ZrO 2 + TiO 2 and, 0-5% MgO; 0-4% ZnO; 0-5% rare earth oxides; 0-5.5% Na 2 O. and 0-4% K 2 O. and 2-34% Li 2 O. and 4-40% Na 2 O+K 2 O + Li 2 O and The microcrystalline glass may be ion-exchanged or non-ion-exchanged glass. The microcrystalline glass according to any one of claims 1 to 16.

18. The composition of the microcrystalline glass is the following oxides in mol % ratio: 45-72% SiO 2 and, 4 to 15% Al 2 O 3 and, 0.4-1.6% B 2 O 3 and, 0.8-1.5% P 2 O 5 and, 0.9 to 4% ZrO 2 + TiO 2 and, 0.1 to 2% MgO; 0.9 to 3.0% ZnO; 0.01 to 1% rare earth oxide; 0-5.5% Na 2 O. and 0-4% K 2 O. and 10-34% Li 2 O. and 15-40% Na 2 O+K 2 O + Li 2 O and The microcrystalline glass may be ion-exchanged or non-ion-exchanged glass. The microcrystalline glass of claim 17.

19. The rare earth oxide is CeO 2 , Y 2 O 3 , La 2 O 3 , Ta 2 O 3 , Tm 2 O 5 and Nd 2 O 5 One or more selected from the following:

19. The microcrystalline glass according to claim 17 or 18.

20. The color additive is 0.5 mol% or more of CoO and / or Cr in terms of the molar content relative to the total components of the glass. 2 O 3 Contains The microcrystalline glass according to any one of claims 1 to 19.

21. The color additive is Fe 2 O 3 , NiO or MnO 2 Contains 1 mol% or more of one or more selected from the following: The microcrystalline glass according to any one of claims 1 to 20.

22. 1) coating a microcrystalline glass with a Si—O containing oxide or mixed silicon oxide layer to form a primer layer on the surface of the microcrystalline glass; Step 2) of coating an intermediate layer on the surface of the undercoat layer obtained in step 1); and step 3) of coating a water- and oil-repellent layer on the surface of the intermediate layer obtained in step 2). The method for producing microcrystalline glass according to any one of claims 1 to 21.

23. A display for a mobile phone, a display for a tablet, a display for a notebook, a portable digital device, a portable game machine, an in-vehicle display, a windshield, or a camera, comprising the microcrystalline glass according to any one of claims 1 to 21.